Principal Management in Improving Teacher Performance for School Program Success: A Comparative Case Study of Two Elementary Schools in Indonesia - Vivi Meilani; Nandang Koswara (Journal of Innovation and Research in Primary Education, 2026)
Principal management plays a critical role in improving teacher performance and ensuring school program success, yet understanding of how management practices function across varied elementary school contexts remains limited. This study examined principal management in improving teacher performance through the PDCA (Plan-Do-Check-Act) framework at two elementary schools in Cianjur Regency, West Java, Indonesia. A qualitative descriptive case study design was employed, with data collected through semi-structured interviews, passive participant observation, and documentary analysis. Research participants comprised school principals and teachers from SD Negeri Nusa Indah Cipanas and SD Negeri Gadog Pacet. Data were analyzed using Miles et al.'s (2014) interactive model, with credibility ensured through triangulation, member checking, and peer debriefing. Findings revealed distinct yet effective management approaches: SDN Nusa Indah demonstrated systematic, participatory leadership emphasizing structured planning, formal supervision, and evidence-based evaluation, while SDN Gadog exhibited transformational leadership prioritizing relational engagement, personalized guidance, and adaptive implementation. Both approaches successfully improved teacher performance through continuous improvement orientations adapted to institutional contexts. Management effectiveness emerges from contextual alignment between leadership practices and institutional realities rather than adherence to singular optimal models, suggesting that both systematic and flexible approaches can generate meaningful teacher development when authentically implemented with continuous improvement orientations.